2015
DOI: 10.3889/oamjms.2015.090
|View full text |Cite
|
Sign up to set email alerts
|

Orthostatic Reactivity in Patients with Ischemic Stroke in the Chronic Period

Abstract: AIM:This study aims to trace the influence of specialized kinesitherapeutic methodology (SKTM) on orthostatic reactivity in patients with ischemic stroke in the chronic period (ISChP).MATERIAL AND METHODS:An active orthostatic test is used for the evaluation of the orthostatic reactions. The arterial blood pressure and heart rate were defined in the 10 minutes of supine position, before and after 1, 5 and 10 minutes of active upright position. The orthostatic autoregulation is evaluated four times - at the beg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…The findings from the ARIC study showed a higher rate of lacunar stroke among patients with orthostatic rise or fall in blood pressure compared to patient without orthostatic changes in BP [ 20 ]. Other studies have also pointed to the same findings in line with more advanced deep white matter lesions among these patients [ 9 , 17 , 27 ].…”
Section: Discussionsupporting
confidence: 81%
“…The findings from the ARIC study showed a higher rate of lacunar stroke among patients with orthostatic rise or fall in blood pressure compared to patient without orthostatic changes in BP [ 20 ]. Other studies have also pointed to the same findings in line with more advanced deep white matter lesions among these patients [ 9 , 17 , 27 ].…”
Section: Discussionsupporting
confidence: 81%
“…According to the pathogenesis, stroke can be divided into subtypes including hemorrhagic stroke and ischemic stroke. As the dominant type of stroke, ischemic stroke accounts for about 80 % of all stroke cases [5][6][7] . An ischemic stroke is caused by insufficient oxygen and blood supply to the brain, which can be caused by a variety of reasons, and in turn leads to brain tissue necrosis.…”
Section: Introductionmentioning
confidence: 99%
“…It seriously affects the quality of life of patient and also brings huge economic pressure on the family and society ( 1 3 ). Clinically, stroke is divided into ischemic stroke and hemorrhagic stroke, where the ischemic stroke rate accountes for ~80% of the incidences of stroke ( 4 6 ). The occurrence of ischemic stroke is due to the lack of cerebral blood supply and oxygen caused by various reasons, resulting in brain tissue necrosis.…”
Section: Introductionmentioning
confidence: 99%